KEUNTUNGAN KOMPETITIF ORGANISASI DALAM PERPSEKTIF RESOURCES BASED VIEW (RBV) - Leonardus Ricky Rengkung (AGRI-SOSIOEKONOMI, 2015)
The uncertaintity and environmental dynamics faced by an organization are highly correlated with the firm’s presence in the organization environment.  Every organization has to an ability to analyze the organization environment in finding and maintaining its competitive advantage. There are some perspectives explaining about the relationship an organization and its environment, one of them is Resources-Based View (RBV). This Resources-Based View (RBV) is a perspective of strategic management focusing on organization level resources, having organization idiosyncratic resources and maximizing the overall resources of organization compared to competitor.  These resources can be a source of relational rents and competitive advantage. The RBV theorizes that the accumulation of resource stocks, that are valuable, rare, imperfectly imitable and non-subsitutable.  The resource-based view of the firm provides a useful perspective for explaining firm growth and sustainable competitive advantage. The purpose of this paper is to explain how an organization in finding and maintaining the competitive advantage in the aspect of Resources-based View (RBV).